2015
DOI: 10.7314/apjcp.2014.15.23.10187
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP39A1, RUNX2 and Oxidized Alpha-1 Antitrypsin Expression in Relation to Cholangiocarcinoma Progression

Abstract: Cytochrome P450 (CYP) enzymes are a large family of constitutive and inducible mono-oxygenase enzymes that play a central role in the oxidative metabolism of both xenobiotic and endogenous compounds. Several CYPs are involved in metabolism of oxysterols, which are cholesterol oxidation products whose expression may be dysregulated in inflammation-related diseases including cancer. This study focused on CYP39A1, which can metabolize 24-hydroxycholesterol (24-OH) that plays important roles in the inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Contrary to the results of the present study, an association of CYP7B1 downregulation with poor overall survival of patients with ER+ breast carcinoma was previously reported . Similarly, CYP39A1 hypermethylation predicted poor prognosis in patients with ovarian carcinoma, and low CYP39A1 expression was associated with metastasis and poor prognosis of patients with cholangiocarcinoma . Both enzymes are 7‐hydroxylases, which catabolize and thus reduce the levels of 24‐hydroxycholesterol (CYP39A1), 25‐hydroxycholesterol and 27‐hydroxycholesterol (CYP7B1) in cells .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the results of the present study, an association of CYP7B1 downregulation with poor overall survival of patients with ER+ breast carcinoma was previously reported . Similarly, CYP39A1 hypermethylation predicted poor prognosis in patients with ovarian carcinoma, and low CYP39A1 expression was associated with metastasis and poor prognosis of patients with cholangiocarcinoma . Both enzymes are 7‐hydroxylases, which catabolize and thus reduce the levels of 24‐hydroxycholesterol (CYP39A1), 25‐hydroxycholesterol and 27‐hydroxycholesterol (CYP7B1) in cells .…”
Section: Discussioncontrasting
confidence: 99%
“…37 Similarly, CYP39A1 hypermethylation predicted poor prognosis in patients with ovarian carcinoma, 38 and low CYP39A1 expression was associated with metastasis and poor prognosis of patients with cholangiocarcinoma. 39 Both enzymes are 7-hydroxylases, which catabolize and thus reduce the levels of 24-hydroxycholesterol (CYP39A1), 25-hydroxycholesterol and 27-hydroxycholesterol (CYP7B1) in cells. 24 Interestingly, deletion of CYP7B1 in xenograft models was associated with increased tumour growth and higher circulating levels of 27-hydroxycholesterol, an agonist of ER in breast carcinoma cells.…”
Section: T a B L E 3 (Continued)mentioning
confidence: 99%
“…We observed a 3.70-fold downregulation CYP39A1 in melanomas ( Figure 2 and Table 3 ). Little is known about CYP39A1 gene expression in skin, but low CYP39A1 expression correlated with increased inflammation and metastasis in cholangiocarcinoma [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhang et al found that 1,2-dichloropropane, a carcinogenic paint remover, could influence the proliferation and apoptosis of cholangiocytes and this effect is mediated through CYP450 [61]. Moreover, Khenjanta et al found that CYP39A1 was down regulated in 70% of CCA patients and low expression of CYP39A1 demonstrated a significant correlation with metastasis [62]. However, the mechanisms of methylation regulation mechanism for these CYP enzymes are still unknown.…”
Section: Discussionmentioning
confidence: 99%